Interaction of ambrisentan with clarithromycin and its modulation by polymorphic SLCO1B1 - Markert, Christoph; Hellwig, Regina; Burhenne, Jürgen; Hoffmann, Michael Marcus; Weiß, Johanna; Mikus, Gerd; Haefeli, Walter E. (European journal of clinical pharmacology, 2013)
We assessed the effect of cytochrome P450 (CYP) 3A4 and the OATP1B1 inhibitor clarithromycin on ambrisentan steady-state kinetics and its relationship to the SLCO1B1*15 haplotype in healthy volunteers.